Characterization of signalling cross-talk between the EP2 and FP receptors in endometrial epithelial cells - Abera, Aron Berhanie (Division of Medical Biochemistry, 2014)
Uterine fibroids are benign tumors that arise from the smooth-muscle uterine cells (myometrium) and are the most common uterine disorder occurring in as many as 30% of women over 35 years of age. Despite their frequent occurrence, the etiology of uterine fibroids is not well elucidated. Several studies have shown that numerous tumors can be regulated by cyclooxygenase (COX) enzyme products but their role in uterine fibroids is not well established. The initial aim of the study was to determine the expression level of COX enzymes and prostaglandin receptors in fibroids and autologous myometrium samples from women with fibroids. Real-Time reverse-transcriptase polymerase chain reaction (RT-PCR) revealed that the expression of COX enzymes, EP1, EP2 and EP4 prostanoid receptors and prolactin were not significantly altered while the EP3 subtype receptor was significantly down-regulated in fibroids compared to adjacent myometrium samples. The EP3 receptor has a protective role in tumor development suggesting the role for down-regulation of the receptor in uterine fibroids pathology. In addition, the expression of COX enzymes, prostaglandin receptors and prostaglandin-mediated genes were assessed in endometrium samples from women with and without uterine fibroids in different stages of the menstrual cycle. COX-2 and interleukin-8 (IL-8) mRNA expressions were significantly higher in both proliferative stage and early-mid secretory, EP2 receptor and IL-11 were elevated in the proliferative stage, vascular endothelial growth factor (VEGF) was highly expressed in the early-mid secretory phase while FP receptor was up-regulated in all stages of the menstrual cycle in endometrium samples from women with fibroids. These data suggest that up-regulation of COX-2 and prostaglandin receptors (EP2 and FP) in endometrium can induce expression of angiogenic and mitogenic factors such as VEGF, IL-8 and IL-11 which might act in a paracrine manner on neighboring myometrial/fibroid tissue to promote angiogenesis and facilitate tumor growth. XVII Furthermore, since EP2 and FP receptors were up-regulated in the proliferative phase of endometrium from uterine fibroid patients and the receptors are co-expressed in endometrial adenocarcinoma (Ishikawa) cells, this study investigated a possible cross-talk that influences intracellular signalling by using Ishikawa cells stably expressing the EP2 and FP receptors (FPEP2 cells) as a model cell line. Real-Time RT-PCR, Western blot analysis and immunofluorescence microscopy confirmed stable expression of the EP2 and FP receptors in FPEP2 cells localized to the perinuclear and plasma membrane. Using FPEP2 cells, the integrated effect of Butaprost (EP2 receptor ligand) and PGF (FP receptor ligand) co-administration on inositol phosphate (IP3) and adenosine 3-,5-cyclic monophosphate (cAMP) release was assessed to study a possible heterologous-interaction or cross-talk between the EP2 and FP receptors. The study showed that in FPEP2 cells, PGF alone does not alter cAMP production, but in combination with Butaprost augments EP2 receptor-mediated cAMP release. PGF-mediated potentiation of cAMP release was abolished by antagonism of the FP receptor, inhibition of phospholipase C (PLC) and IP3-receptor whereas inhibition of protein kinase C (PKC) had no effect suggesting the cross-talk is mediated by FP receptor activation of IP3 release. Moreover, inhibition of calcium effectors using calmodulin antagonist (W7) or Ca2+/calmodulin-dependent kinase II (CaMK-II) inhibitor (KN-93) abolished PGF potentiation of Butaprost-mediated cAMP release. Using short interfering RNA (siRNA) molecules targeted against the adenylyl cyclase 3 (AC3) isoform, the study showed the isoform to be responsible for the cross-talk between the FP and EP2 receptors. In order to determine the integrative effects of the EP2 and FP receptors co-activation on gene expression, a whole genome array profiling in FPEP2 cells in response to Butaprost and/or PGF was performed. The gene array revealed 228 genes that are regulated by co-activation of the EP2 and FP receptors that are involved in cell morphology, proliferation and differentiation. XVIII In addition, co-activation of EP2 and FP receptors with their respective ligands enhanced or repressed a set of EP2 receptor-regulated genes. One of the genes identified, SAT1 (Spermidine/ N1-acetyltransferase), was regulated by the EP2 and FP receptors cross-talk via the calcium sensitive AC3 isoform. SAT1, with known role in regulation of tumorigenesis was also up-regulated in the proliferative stage of endometrium samples from women with uterine fibroids suggesting the EP2 and FP receptor cross-talk characterized in vitro can also happen in vivo. In conclusion, this study reports that COX-2, EP2 and FP receptors, VEGF, IL-8, IL-11 and SAT1 are up-regulated in endometrium from women with uterine fibroids. These genes play a major role in development of fibroids by facilitating angiogenesis and cell growth and by inhibiting apoptosis via autocrine/paracrine mechanisms. In addition, this study demonstrates that co-activation of the EP2 and FP receptors results in enhanced release of cAMP via the FP receptor-G +-q-Ca2+-calmodulin pathway by activating the calcium-sensitive AC3 isoform and modulates a molecular switch which alters the trans-activation of a subset single-receptor induced genes that have important functions in the pathogenesis of reproductive pathologies.